Intracellular Viral RNA Species in Mouse Cells Nonproductively Transformed by the Murine Sarcoma Virus - Tsuchida, Nobuo (1974)
The size and quantity of virus-specific RNA in five non-virus-producing mouse cells transformed by the Moloney isolate of murine sarcoma virus (MSV) was determined. Hybridization of RNA from transformed cells with the [(3)H]DNA product of the RNA-directed DNA polymerase of the murine sarcoma-leukemia virus was used to detect and quantitate virus-specific RNA. The amount of virus-specific RNA in non-virus-producing cells was less than one-sixth of that found in virus-producing cells. A striking correlation was found between the amount of intracellular virus-specific RNA and the degree of agglutination by conconavalin A previously reported for the four non-virus-producing NIH/3T3 cell lines (Salzberg and Green, 1974). A major RNA subunit sedimenting at 26 to 28S was detected in all five MSV-transformed non-virus-producing cells. This could represent the RNA genome of defective MSV.